2002
DOI: 10.1046/j.1523-1755.2002.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher urinary IgM excretion in type 2 diabetic nephropathy compared to type 1 diabetic nephropathy

Abstract: The increased urine excretion of IgG and IgM that accompanies albuminuria in type 2 DN suggests that the dominant pathophysiological mechanism of proteinuria in type 2 DN might be an alteration of the size selective properties of the glomerular capillary wall, including the occurrence of non-discriminatory "shunt pathways." The charge selective properties of the glomerular capillary wall seem to be intact in type 2 DN, as indicated by the high IgG2/IgG4 ratio. The mechanisms of proteinuria in type 1 DN seem to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 24 publications
1
39
0
2
Order By: Relevance
“…Although urinary excretion is not a significant route of mAb elimination in healthy subjects, renal excretion of therapeutic mAbs may occur, as it does for endogenous proteins in DM, leading to increased It is known that moderate CKD leads to the urinary excretion of endogenous proteins, such as albumin, that are normally conserved (27). Furthermore, larger proteins, such as IgG (mol radius 5.5 nm) or IgM (mol radius 12 nm) that have limited renal elimination, are known to have higher transport across the glomerular filter with compromised renal function and DN (9). The increased size and density of larger pores, along with increased density of shunts in the glomerular capillary wall, leads to increased concentrations of larger molecules in the urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although urinary excretion is not a significant route of mAb elimination in healthy subjects, renal excretion of therapeutic mAbs may occur, as it does for endogenous proteins in DM, leading to increased It is known that moderate CKD leads to the urinary excretion of endogenous proteins, such as albumin, that are normally conserved (27). Furthermore, larger proteins, such as IgG (mol radius 5.5 nm) or IgM (mol radius 12 nm) that have limited renal elimination, are known to have higher transport across the glomerular filter with compromised renal function and DN (9). The increased size and density of larger pores, along with increased density of shunts in the glomerular capillary wall, leads to increased concentrations of larger molecules in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of microalbuminuria and macroalbuminuria is significant with T2DM, only a limited number of studies have evaluated the alteration in renal elimination and urinary concentrations of proteins and macromolecules such as IgG (9,10). In one study, Pima Indians with T2DM and DN demonstrated a greater than twofold increase in urinary IgG concentrations compared to individuals without significant microalbuminuria (10).…”
Section: Introductionmentioning
confidence: 99%
“…According to the SEM images of a gold-coated probe (radius of tip apex is 35 nm), and according to the dimensions of a cross linker SPDP (~0.7 nm in length) and an antibody (IgM, 24 nm in length) [23], the diameter of the tip contact area is ~120 nm, which correlates to approximate one pixel (125 nm) in a 4×4 µm 2 affinity map. The antibody modified tip scans pixel by pixel to achieve an affinity map.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be relevant to the pathogenesis of proteinuria in diabetic states. Diabetic nephropathy is associated with structural alterations that contribute to the increased permeability of the glomerular capillary wall to macromolecules (21)(22)(23)(24)(25). The cellular mechanisms leading to loss of permselectivity during progression of diabetic nephropathy are not well characterized.…”
Section: Discussionmentioning
confidence: 99%